Agricultura familiar e mudanças climáticas (Brasil e Espanha):percepções e desafios emergentes da educação ambiental para a saúde planetária - Gonzalez, Aline Costa (2023)
For many decades, human lifestyle has been pushing the planet to its biophysical limits. The disorderly growth of cities, inadequate soil management, large greenhouse gas emissions and the exploitation of natural resources in an unlimited manner has been unbalancing ecosystems and increasing the effects of Climate Change in the world. The context of this study considers the scientific research and predictions that indicate that natural / socio-environmental disasters are increasing in frequency and intensity, bringing food insecurity, human damages and financial losses, especially to the most vulnerable populations, such as family farmers. Thus, this study first aims to research the impacts of socio-environmental disasters in the West of Paraná, using the cities of Cascavel, Foz do Iguaçu and Toledo as parameters. This research is exploratory, documentary and qualitative-quantitative in order to achieve a greater knowledge of the subject and a deeper visualization of the consequences of the Climate Emergency. Secondly, the research uses a descriptive and qualitative approach by capturing the impressions of family farmers in the Western Region of Paraná (Brazil) and Galicia (Spain), through semi-structured interviews and content analysis, in order to understand the perceptions and demands of these social actors on the impacts of Climate Change on food production. The study of these two regions is justified as they both are areas whose family farming is thriving, is traditional, and has great potential where they are geographically located. Finally, through documentary research and narrative investigation to find pedagogical practices of Environmental Education, which can contribute to the creation of educational agendas and Public Policies to face the impacts of Climate Change on the land, in order to improve the quality of life of family farmers, the construction of sustainable and resilient territories and collaboration with planetary health. Thus, by understanding how family farmers perceive these climate changes in their production, it was possible to reflect on the challenges and demands pointed out by them so that they are valued and receive the necessary assistance to continue producing quality food in a sustainable manner, as well as thinking of ways to mitigate the damage and improve the formation of more aware citizens with the autonomy to discuss issues related to the socio environmental crisis. That said, the work sought to add ideas and possibilities for social pedagogical practices, believing that the inclusion of Environmental Education in different areas of society, especially in family farming, plays a fundamental role in the expansion and systematization of knowledge, so that there is a reconnection between human-nature and with everyone's contribution, real transformation takes place so that quality of life is privileged, social inequalities are reduced and climate justice is achieved.